Longitudinal Associations Between Serum Bilirubin Level and Carotid Atherosclerosis Plaque in a Health Screening Population. (May 2023) - Qin, Lu; Li, Lin; Fan, Hongzhen; Gu, Yongsheng; He, Weiliang; Zhang, Kaihua; Sun, Yingru; Zhao, Wannian; Niu, Xiaoli; Wei, Ci; Li, Litao; Wang, Hebo
This study aimed to determine the relationship between bilirubin levels and carotid atherosclerosis (CAS) in the health screening population. After propensity score matching, this retrospective cohort study included 4360 subjects who underwent health examinations regularly in Hebei General Hospital between January 2010 and December 2019 and had no carotid plaque at baseline. After an average follow-up of 26.76 months, the main endpoint Cox regression analysis of carotid plaques was performed. After adjusting the confounding factors, Cox regression analysis showed that when serum total bilirubin (TBIL) and unconjugated bilirubin (UCB) increased by 1 standard deviation (SD), the risk of carotid plaque decreased by 7.30% (95% confidence interval (CI): 2.80–11.60%) and 15.70% (95% CI: 11.40–19.80%), respectively. When conjugated bilirubin (CB) increased by 1 SD, the risk of carotid plaques increased by 24.3% (95% CI: 19.7–29.0%). TBIL and UCB levels were negatively associated with CAS, and CB levels were positively associated with CAS.